2020
DOI: 10.1038/s41467-020-17812-2
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy-entropy compensation of atomic diffusion originates from softening of low frequency phonons

Abstract: Experimental data accumulated over more than 120 years show not only that diffusion coefficients of impurities ordinarily obey the Arrhenius law in crystalline solids, but also that diffusion pre-exponential factors measured in a same solid increase exponentially with activation energies. This so-called compensation effect has been argued to result from a universal positive linear relationship between entropic contributions and energy barriers to diffusion. However, no physical model of entropy has ever been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…45 Therefore, N1 has been interpreted as continuum of donor states at the CIS surface 42 or an injection/extraction barrier. 46,47 In view of the evidence for Cu migration in CIS, N1 showing up with same rates for τ 1 and τ 2 independent of any transport layers, and ionic defects often following the Meyer−Neldel rule, 7 we propose that the N1 signal in CIS corresponds to ionic migration, likely to Curelated defects.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…45 Therefore, N1 has been interpreted as continuum of donor states at the CIS surface 42 or an injection/extraction barrier. 46,47 In view of the evidence for Cu migration in CIS, N1 showing up with same rates for τ 1 and τ 2 independent of any transport layers, and ionic defects often following the Meyer−Neldel rule, 7 we propose that the N1 signal in CIS corresponds to ionic migration, likely to Curelated defects.…”
mentioning
confidence: 69%
“…Using iodide partial pressure investigations, it was deduced that the halide ion is the most mobile. 4,5 Furthermore, it was shown that the mobile ions follow the Meyer−Neldel rule 6,7 and that HaPs are capable of self-healing after being damaged. 8,9 As a result, Rakita et al 10 stated that HaPs "are likely an example of a class of materials that cannot support static bulk defect densities significantly above thermodynamically-dictated densities.…”
mentioning
confidence: 99%
“…46,55 The physical origin of this dependence of diffusion prefactor on activation energy is still not resolved, although recently an explanation based on compensation effect due to loosening of crystalline lattices' elastic moduli at transition states (Zener's model) has been proposed. 56 Because of the presence of an internal electric field, ions accumulate at the interfaces between the perovskite active layer and the transport layers, 57 which leads to the formation of Debye layers at these interfaces. When anions and cations are present, 46 Debye layers form at both interfaces to the transport layers.…”
Section: Acs Energymentioning
confidence: 99%
“…The compensation effect has been largely ascribed to softening of low-frequency m modes at the transition state relative to the initial state based on diffusion studies in silicon and aluminum. 31 In the present case, however, the change in was mainly determined by 0 the change in the entropy of vacancy formation, which in turn had a significant contribution from the vibrational entropy of hydrogen (Supplementary Fig. 2).…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 51%